2010
DOI: 10.1051/0004-6361/201014392
|View full text |Cite
|
Sign up to set email alerts
|

Search for extratidal features around 17 globular clusters in the Sloan Digital Sky Survey

Abstract: Context. The dynamical evolution of a single globular cluster and also of the entire Galactic globular cluster system has been studied theoretically in detail. In particular, simulations show how the "lost" stars are distributed in tidal tails emerging from the clusters. Aims. We investigate the distribution of Galactic globular cluster stars on the sky to identify such features as tidal tails. The Sloan Digital Sky Survey provides consistent photometry of a large part of the sky to study the projected two-dim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
110
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(120 citation statements)
references
References 73 publications
8
110
2
Order By: Relevance
“…Although simulations of the dynamical evolution of GCs is still not completely clear (D'Ercole et al 2008;Baumgardt et al 2008;Carretta et al 2010), it is accepted that they lose stars. Observations of extratidal structures of GCs (Martínez Delgado et al 2004;Law & Majewski 2010;Jordi & Grebel 2010) in the Galactic halo confirm this result. But the question of how many field halo stars come from disrupted GCs is still under debate (e.g.…”
Section: Consequencesmentioning
confidence: 65%
See 1 more Smart Citation
“…Although simulations of the dynamical evolution of GCs is still not completely clear (D'Ercole et al 2008;Baumgardt et al 2008;Carretta et al 2010), it is accepted that they lose stars. Observations of extratidal structures of GCs (Martínez Delgado et al 2004;Law & Majewski 2010;Jordi & Grebel 2010) in the Galactic halo confirm this result. But the question of how many field halo stars come from disrupted GCs is still under debate (e.g.…”
Section: Consequencesmentioning
confidence: 65%
“…Yong et al 2008;Boley et al 2009;Martell & Grebel 2010;Carretta et al 2010). Recently, Jordi & Grebel (2010) detected tidal features using the same data set as this study. This means that this particular sample of clusters is being evaporated into the Galactic halo.…”
Section: Consequencesmentioning
confidence: 96%
“…Odenkirchen et al (2003) were the first to show evidence of inhomogeneities in Pal 5's streams, characterized by stellar density gaps (underdense regions) and clumps (overdense regions), particularly visible in the trailing stream, with the most evident and massive overdensities found between 100 and 120 arcmin Appendices A and B are available in electronic form at http://www.aanda.org from the cluster center. The presence of density fluctuations along the stream has been successively confirmed by Grillmair & Dionatos (2006) and Jordi & Grebel (2010), and the nature of these clumps has been long debated. Already before the observations of Pal 5's tidal stream, Combes et al (1999) showed the presence of small clumps in the tidal tails of simulated GCs, and attributed their formation to strong gravitational shocks suffered by the system at each disk crossing.…”
Section: Introductionmentioning
confidence: 98%
“…This is that the truncation prescription affects the density distribution in the outer parts of the models significantly. This general point is even more important if we are interesting in modeling the outermost regions of globular clusters (and the issues that are often discussed under the name of studies of "extra-tidal light", e.g., see Jordi & Grebel 2010).…”
Section: Choice Of the Distribution Functionmentioning
confidence: 99%